2018
DOI: 10.1007/s11606-018-4540-5
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting the Patient’s Agenda- Secondary Analysis of Recorded Clinical Encounters

Abstract: Clinicians seldom elicit the patient's agenda; when they do, they interrupt patients sooner than previously reported. Physicians in specialty care elicited the patient's agenda less often compared to physicians in primary care. Failure to elicit the patient's agenda reduces the chance that clinicians will orient the priorities of a clinical encounter toward specific aspects that matter to each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(104 citation statements)
references
References 32 publications
2
93
0
Order By: Relevance
“…Likewise, a screening tool may uncover multiple social risks, such as food, housing, and utilities instability, but the patient may tell her provider that her most pressing social need is to find a safe place to stay, away from a violent male partner. Failing to understand the patient's perspective—a common failure even within the scope of traditional biomedical care—could lead to the wrong immediate treatment.…”
Section: Terms and Distinctionsmentioning
confidence: 99%
“…Likewise, a screening tool may uncover multiple social risks, such as food, housing, and utilities instability, but the patient may tell her provider that her most pressing social need is to find a safe place to stay, away from a violent male partner. Failing to understand the patient's perspective—a common failure even within the scope of traditional biomedical care—could lead to the wrong immediate treatment.…”
Section: Terms and Distinctionsmentioning
confidence: 99%
“…In the 1980s, research reported that the majority of physicians interrupted patients within 18 seconds of the conversation . The latest study on this topic shows an average of 11 seconds to interruption by a physician …”
Section: Discussionmentioning
confidence: 99%
“…17 The latest study on this topic shows an average of 11 seconds to interruption by a physician. 18 In contrast, chaplain listening appears to involve a substantial amount of time, with one large adult study reporting time spent between five minutes and over two hours. 19 Given that patient satis-faction is largely dependent on the quality of communication with the medical team, it is possible that deep listening is the means by which patient satisfaction is improved by visits from a chaplain.…”
Section: Discussionmentioning
confidence: 99%
“…26 SIBR can address many of these barriers through simple modifiable measures such as making it easy to anticipate when the round will occur, prompting clinician use of appropriate language, assisting patients to formulate questions and prompting behaviours to facilitate participatory decision-making. 29 Conversely, with SIBR, behaviours such as explaining clinical issues to patients were more frequently observed. However, clinician behaviours to facilitate participation were inconsistent.…”
Section: Patient Engagement and Participationmentioning
confidence: 99%